Effect of aflibercept in insufficient responders to prior anti-VEGF therapy in neovascular AMD - Fassnacht-Riederle, Heidi; Becker, Matthias D. (Graefe's archive for clinical and experimental ophthalmology, 2014)
Evaluation of three aflibercept injections at 4-week intervals in patients with neovascular AMD showing an “insufficient anatomic response” to prior anti-VEGF therapy with ranibizumab or bevacizumab.
Gesehen am 22.09.2020